PREVENTT: preoperative intravenous iron to treat anaemia in major surgery: study protocol for a randomised controlled trial. Issue 1 (December 2015) - Richards, Toby; Clevenger, Ben; Keidan, Jane; Collier, Tim; Klein, Andrew; Anker, Stefan; Kelly, John
Abstract Background Anaemia is common in patients undergoing major surgery. The current standard of care for patients with low haemoglobin in the peri-operative period is blood transfusion. The presence of preoperative anaemia is associated with an increased likelihood of the patient receiving peri-operative transfusion and worsened outcomes following surgery, more post-operative complications, delayed recovery and greater length of hospital stay. Intravenous iron, if applied in the preoperative setting, may correct anaemia by the time of surgery and reduce the need for blood transfusion and improve outcomes. Methods/Design PREVENTT is a phase III double-blind randomised controlled trial that will compare the use of intravenous ferric carboxymaltose (dose 1000 mg) with placebo 10–42 days before major open abdominal surgery in 500 patients with anaemia (haemoglobin < 120 g/L). The primary outcome measure will be the need for blood transfusion and secondary endpoints will include post-operative recovery, length of hospital stay, health care utilisation and cost analysis. Trial registration ISRCTN67322816 – registered 9 October 2012. ClinicalTrials.gov identifier:NCT01692418 .